The development and feasibility of the occupational therapy-led `Work and Cancer' intervention for women living with and beyond breast cancer - Algeo, Naomi (Trinity College Dublin. School of Medicine. Discipline of Occupational Therapy, 2022)
Background: Increased survivorship has prompted focus on optimising quality of life for those living with and beyond cancer, including reintegration into work. Despite frequently cited return-to-work barriers for women living with and beyond breast cancer, there are no conclusive work-focused interventions. The aim of this research was to design and assess the feasibility of a work-focused intervention to support return-to-work for women living with and beyond breast cancer. Methodology: A four-phase study, following the Medical Research Council framework for complex interventions, included three development phases; (I) exploration of barriers and facilitators in return-to-work post-breast cancer diagnosis using a qualitative-descriptive design, (II) a systematic review and meta-analysis reviewing interventions that support return-to-work, and (III) a nominal group technique consensus study prioritising intervention content and delivery. A single-arm feasibility study with qualitative-descriptive design evaluated intervention feasibility and acceptability (Phase IV). Results: Phase I identified a diverse range of barriers and enablers in return-to-work that could be amenable to change through rehabilitation. Phase II indicated a lack of methodologically rigorous and effective work-related intervention studies for women with breast cancer. Phase III prioritised a six-week intervention with group and individual sessions. Phase IV found the intervention to be feasible and acceptable to women living with and beyond breast cancer with 100% retention and 90% adherence. Conclusion: A six-week online intervention to support women living with and beyond breast cancer in navigating work post-cancer was developed and found to be both feasible and acceptable. High adherence and retention rates were observed. A larger scale evaluation is warranted to determine the effectiveness of the intervention on work and other health-related outcomes.
APPROVED
Keywords: Occupational Therapy; Employment; Reintegration; Oncology; Rehabilitation; Cancer Survivorship